Debate, Critical Thinking Disposition, and Self-confidence: Do They Contribute to Speaking Proficiency? - Miftaqur Rochmah Ayu Saputri; Rohmani Nur Indah; Fathor Rasyid (Premise: Journal of English Education and Applied Linguistics, 2022)
Critical thinking, self-confidence, and speaking skills are fundamental skills, and debate is one of the methods that enhance these skills. This study investigates the direct and indirect contributions of debate, critical thinking disposition, and self-confidence to improve speaking skills. The design of this research is path analysis and uses AMOS 24 in the data analysis. 67 out of 72 students who participated in the debate competition at East-Java English Club 4 became the sample of this research. Questionnaires were used to determine students' perceptions of debate, critical thinking disposition, and self-confidence. In addition to the questionnaire, a speaking test using the Student Oral Language Observation Matrix (SOLOM) was used to measure speaking proficiency. The findings show a significant direct contribution of debate to students' critical thinking, self-confidence, and speaking skills. For indirect contribution, there is a significant contribution from debate to speaking skills through critical thinking and a significant contribution from debate to speaking skills through self-confidence. From these results, recommendations for future researchers are about how to implement the in-class debate method in the realm of experimental research to develop the three variables previously mentioned.